2022
DOI: 10.1101/2022.01.17.22269262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuroanatomical correlates of polygenic risk for Parkinson’s Disease

Abstract: Parkinson's Disease (PD) is a progressive neurodegenerative disorder with a long prodromal course. Most cases are sporadic but a polygenic risk score (PRS) recently constructed from genome-wide association studies (GWAS) has identified 90 variants that contribute to disease vulnerability. While some of the genes identified affect known disease pathways, the mechanisms by which genetic risk renders individuals vulnerable remain mostly unknown. Understanding how PD PRS manifests in the brain could inform disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 84 publications
3
6
0
Order By: Relevance
“…Unlike cortical thickness where thinning is generally the event expected from aging and neurodegeneration, 103 surface area was increased in certain areas compared to healthy individuals, 15 as previously found in a population-based MRI study of healthy adults showing that a higher genetic risk of Parkinson’s disease is associated with greater cortical surface area. 104 In our study, greater cortical surface area was associated with a greater expression of genes involved in the inflammatory response. Similarly, virtual histology revealed that increased surface area related to genes associated with astrocytes and microglia.…”
Section: Discussionsupporting
confidence: 55%
“…Unlike cortical thickness where thinning is generally the event expected from aging and neurodegeneration, 103 surface area was increased in certain areas compared to healthy individuals, 15 as previously found in a population-based MRI study of healthy adults showing that a higher genetic risk of Parkinson’s disease is associated with greater cortical surface area. 104 In our study, greater cortical surface area was associated with a greater expression of genes involved in the inflammatory response. Similarly, virtual histology revealed that increased surface area related to genes associated with astrocytes and microglia.…”
Section: Discussionsupporting
confidence: 55%
“…Interestingly, the cortical chromosome 17 risk variant signature showed a distinct spatial profile and displayed a dichotomy with cortical thinning but increased cortical surface area. Such a pattern has been reported in some neurodegenerative conditions like Parkinson’s Disease 37 and points to shape variation such as increased gyrification. The nature of these dissociated cortical changes remains unknown but has been linked to putative neurodevelopmental differences 38 as cortical thickness and area show very little genetic correlation 39 .…”
Section: Discussionsupporting
confidence: 66%
“…15 This is similar to a population-based MRI study of healthy adults showing that a higher genetic risk of PD is associated with greater cortical surface area. 51 In our study, we showed that greater cortical surface area in iRBD was associated with a greater expression of genes involved in the inflammatory response. Similarly, our virtual histology analysis showed that increased surface area related to genes associated with astrocytes and microglia.…”
Section: Discussionsupporting
confidence: 49%
“…53 Cortical surface area is also subject to tangential expansion due to cellular processes such as synaptogenesis, gliogenesis, and myelination that occur over a longer period than the processes involved in cortical thickness. 54 Cortical thickness and surface area are differentially affected in PD and iRBD patients and in healthy adults with a higher risk of PD, 15,51,55 but the biological explanation for this remains unclear. Based on the enrichment patterns identified in this study, it can be hypothesized that unlike thickness, the surface area changes, which related to inflammation, astrocytes and microglia, may not necessarily relate to pathological effects occurring locally.…”
Section: Discussionmentioning
confidence: 99%